Die Relevanz der Vorstellungslehre von Kazimierz Twardowski für die Repräsentationale Theorie des Geistes - Anita Pacholik-Żuromska (Analiza i Egzystencja)
The aim of this paper is to compare the Representational Theory of Mind (RTM) with the phenomenological approach to the mental. To this end, I relate the philosophical views of Franz Brentano and Kazimierz Twardowski to the theses of the Represen- tational Theory of Mind, which was written by Jerry Fodor. I refer in particular to Twardowski, who conducted his research with a phenomenological background in the field of descriptive psychology using the method of conceptual analysis. His approach corresponds to the analytical philosophy of mind, which, among other things, asks about the nature of representations. I compare Twardowski’s view on the structure of mental phenomena and the mechanism of their functioning with the RTM formulated by Jerry Fodor. I argue that applying Twardowski’s concept instead of Frege’s, which Fodor uses, would correct RTM accordingly and solve the problems with intentional and phenomenal content, because RTM does not necessarily require the propositional form of content.